SOIL PHYSICAL CONSTRAINTS AND THEIR EFFECT ON MORPHOLOGICAL CHARACTERS OF COCONUT (Cocos nucifera L. ) ROOTS - L P Vidhana Arachchi; Yaspa P A J; Mapa R B; Somapala H. (International Coconut Community, 2000)
The objective of the study was to (1) evaluate land suitability for coconut (cocos nucifera L.) production in relation to soil physical properties, (2) identify the soil physical constraints and (3) study their effect on the morphological adaptation of coconut roots. Soil physical properties were found to be significantly related to coconut yield (R2=81.37; p<0.01). Multiple regression with cluster analysis of soil physical properties vs coconut yield enabled classification of soil series into three major groups namely (a) highly (b) moderately and (c) less productive series. It was observed that the high soil compaction which limited the available water and aeration capacity of soils resulted in retardation of the activity of coconut roots. Water stress due to soil compaction was found to induce production of more inactive roots by suberization and dehydration processes. Scanning electron microscopic image showed that soil compaction and water stress, reduced the cell volume per unit area of the absorption zone and the number of pores in respiratory organs of coconut roots resulting in retardation of water and nutrient absorption, and air exchange processes. This in turn malfunctions of absorption cells and respiratory organs of roots resulted in retardation of growth of coconut seedlings. The practical importance of these findings in formulation of land suitability maps for coconuts is discussed.